P2.185 HPV and Pregnancy: The Controversial Role of Maternal-Fetal Transmission. (13th July 2013) - Skerlev, M; Sirotković-Skerlev, M; Ljubojević, S
Abstract : Background and open questions: Human papillomavirus (HPV) - associated pathology represents one of the major problems among STIs mostly due to the high recurrence rate, difficult eradication and oncogenic potential. Young, sexually active population in the generative period is mostly affected. Pregnancy may definitely foster the development of latent or manifest HPV infections and may enhance the development of the pathology which then often recedes in the postpartum. The data reported in the literature on the relationship between HPV and pregnancy are highly controversial. A number of different opinions emerge regarding the possibility of maternal-fetal virus transmission. This discrepancy depends on the diagnostic techniques, the clinical history and the period of pregnancy when the sample is collected. The possible maternal-fetal transmission of the virus might be considered, for example, the main factor responsible for juvenile laryngeal papillomatosis, and the onset of the genital warts in children's age (apparently more often than the child's sexual abuse which should not be neglected either!). Many authors report an initial presence of HPV in newborns which often disappears within 6 months after birth. Conclusion: According to the most recent vaccination recommendations, HPV vaccines are not recommended for use in pregnant women. However, pregnancy testing is not needed before vaccination. If a woman is found to be pregnant after initiating the vaccination series, no intervention is needed; the remainder of the 3-dose series should be delayed until completion of pregnancy. Providing the controversies that still exist, modes of HPV transmission in pregnancy should be investigated more detailfully in order to get clearer picture and a fuller awareness of the preventive measures. It can be concluded that, in this very moment, there is a need for a coordinated effort of health professionals and policymakers to ensure successful implementation of vaccination programmes for both women and men.